Smart display indicator / Muhammad Faiz Anuar, Abdul Salam Muda and Ahmad Syaqiq Ahmad Mizam - Anuar, Muhammad Faiz; Muda, Abdul Salam; Ahmad Mizam, Ahmad Syaqiq (2013)
Idea to design The Smart Display Indicator is come from our observation about students nowadays had a difficulty to meet with their lecturer especially in their room. The primary problems is students must go to their lecturer room to get to know whether their lecturer in the room or not. This situation also affect a lecturer to tell about their presence in their room and sometimes it get annoying because a lecturer got to had some rest in their room but get disturbed by their students. By designating the Smart Display Indicator, the students and lecturers do not have to worry how to overcome this situation. The Smart Display Indicator will showing the presence of a lecturer in their room by using the LED in the list names of lecturers at the ground floor of the building and can leave a message that will be display on LCD at the door’s room To achieve this objectives, the structure and system used, should include few criteria such as the wireless system, a short message and the technology design. This final semester project covers both fifth and sixth semester. This is also one opportunity for student to show or to apply their knowledge and skills in manufacturing, programming, installation process and software designation that have been learn before.